What Drives Enterprise Risk Management Disclosure? Evidence from Risk Management Committee, Leverage, Profitability, and Board of Commissioners Size - Alni Rahmawati; Naila Letisha Djasman (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the effect of the risk management committee, leverage, and profitability on enterprise risk management disclosure, with board of commissioners size as a moderating variable, in manufacturing industries listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. This study uses a quantitative approach with 462 samples from 137 companies selected using a purposive sampling technique. Data analysis uses moderated regression analysis with EViews 13 software. The results show that the risk management committee, leverage, and profitability have a positive and significant effect on enterprise risk management disclosure. Board of commissioners size is able to moderate the effect of profitability on enterprise risk management disclosure. This study is expected to provide an academic contribution to the development of financial management science and to broaden scientific understanding of the risk management committee, leverage, profitability, board of commissioners size, and enterprise risk management disclosure. This study also provides practical guidance for management in designing strategies to improve the quality of enterprise risk management disclosure more effectively, as well as understanding for stakeholders regarding the factors that influence such disclosure. This study only uses data from the 2021-2024 period, so the results do not yet fully reflect long-term conditions; therefore, future research is advised to use a longer observation period in order to obtain more comprehensive results.